CREATIVE CONVERGENCE AND FUSION OF FORMS: CROSS POLLINATION OF ART AND LITERATURE IN WESTERN AND INDIAN PERSPECTIVES - Pratibha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the dynamic intersection between art and literature, focusing on the process of cross-pollination, where the two forms influence, enrich, and inspire one another. By examining key movements such as Romanticism, Surrealism, and Modernism, the study highlights how visual art and literary narratives have historically interacted to create new expressions of thought, emotion, and culture. Drawing on examples from Indian and Western traditions, the paper delves into the ways artists and writers borrow techniques, themes, and metaphors from each other, creating hybrid forms that challenge conventional boundaries. Special attention is given to the use of ekphrasis in literature, where art is translated into narrative, and the visual storytelling seen in artistic works that reflect literary themes. This interdisciplinary approach reveals how both art and literature serve as mirrors of societal values and human experiences, transcending medium-specific constraints. The paper argues that this cross-pollination not only diversifies creative expression but also fosters deeper connections between cultures and periods, expanding the scope of interpretation and aesthetic appreciation.